The Translation of Identity Markers in The Arabic Novel Al Shahwan into English (Journal of the College of Languages (JCL), 2025)
The study deals with the translation shortcomings that lead to distortion in the transmission of the cultural identity of Mosul as enshrined in the novel Al-Shahwan, which serves as an accurate mirror of the historical background and heritage of Mosul. The study aims to identify the hurdles that translators pass through their attempt to maintain some aspects of the cultural identity-related to geographic, linguistic, cultural, and historical contents in the process of transferring the texts from Arabic to English. The model used in the research is that of 12 deforming tendencies by Antoine Berman, which serves as a theoretical framework on how to identify and classify translation shortcomings that mostly lead to cultural identity morphosis in translations, among these are over-clarification, expansion, reduction in cultural identity. The study also relies on content analysis and thus compares source texts to last translations in order to identify deficiencies that impact the transmission of cultural identity. The findings refer to very broad deficiencies in conveying Mosul's symbolic and cultural elements, with the end result being a translated text that minimally treats the original message. Such errors include, but are not limited to: over-explanation leading straight into the fray of art and unavailability of regional symbols. The study proposes a number of recommendations for countering these translational failures, e.g. training translators to grasp the symbolic meanings of texts and instituting increased collaboration between authors and translators to facilitate the cultural transference. It also emphasizes the application of analytical models as tools to evaluate translation quality and preserve the cultural integrity of literary works to allow for accurate dissemination of cultural heritage, and preserving it for furture generations.